Age-related cataract: prevention and treatment - I.A. Koroleva; E.A. Egorov (РМЖ "Клиническая офтальмология")
I.A. Koroleva1, E.A. Egorov2 1 City Clinical Hospital No. 15, Moscow, Russian Federation 2 Pirogov Russian National Research Medical University, Moscow, Russian Federation Cataract is the leading cause of blindness and ranks second among the causes of visual impairment in the world. More than 80% of cataract patients live in low-income developing countries. Pathogenesis of cataract development remains poorly studied, despite the many years of interest of scientists to the causes of this disease. Today, one of the dominant theories of cataractogenesis is the theory of oxidative stress. In 80% of cases, visual functions reduced by cataracts can be restored after surgery, but it is essential to consider that this approach to treatment leads to significant economic costs. Studies show that many patients experience anxiety and fear of surgery, which can also lead them to refuse or postpone the decision about the need for surgical intervention. Besides, patients in the older age group may experience contraindications for this operation on the part of the comorbid pathology. In these cases, the task of the ophthalmologist will be the combined prescription of drugs with clinically proven antioxidant and metabolic effects that slow down the development of cataracts, for example, Oftan® Catachrom eye drops.  Key words: lens, opacification, cataract, cataract extraction, eye drops, Oftan Catachrom. For citation: Koroleva I.A., Egorov E.A. Age-related cataract: prevention and treatment. RMJ “Clinical ophthalmology”. 2018;4:194–198.